A Case Study of Analyzing Students’ Focus in Writing - Manik, Ronika Apriyanti; Harahap, Ahmad Fadli (Universitas Muhammadiyah Mataram, 2025)
Maintaining focus in writing is among the underemphasized but critical areas of academic literacy, particularly among English as a Foreign Language (EFL) students. Indonesian EFL learners mostly put more effort into maintaining thematic coherence and logical coherence of writing despite their operationally effective grammatical and lexical control. Although writing pedagogy is a stronghold of language instruction, little has been investigated in Indonesia which seeks to investigate students' capacity to maintain focus, a fundamental skill in guaranteeing coherent and effective texts. This research was prompted by the noted lack of pedagogical focus and empirical investigation of focus in writing, and particularly at the tertiary level. Using a qualitative case study design, the researcher examined the writing of 25 second-semester business management students. Participants were tasked with composing personal narratives and reflecting on their writing experiences. After that, the students' writings were evaluated based on five criteria, such as clarity of main idea, relevance of supporting details, consistency, topic unity, transitions and coherence. Findings reveal that the majority of students demonstrated Limited to Basic proficiency in all five areas with the highest deficiencies observed in topic unity and consistency. Also, most of the students can write sentences but struggle to organize and connect the ideas logically correspond to the theme. The data also shows that the participants faced significant linguistic and cognitive challenges, such in expressing ideas fluently, selecting appropriate vocabulary, and understanding genre-based writing. This study underscores the urgent need for a pedagogical shift that adopt a process-based which constructivist approaches that view writing as a repeated activity involving planning, drafting, reviewing, and revising. Such an approach recognizes that effective writing instruction must extend beyond grammatical correctness and surface-level features.